Effectiveness of stress inoculation training on occupational stress of midwives in healthcare centers of Zahedan in Health Transformation Plan in 2017 - Ali Navidian; Maryam Navaee; Hadis Kaykha (Wolters Kluwer Medknow Publications, 2019)
INTRODUCTION: Occupational stress is a main problem of healthcare workers, which significantly affects their professional and personal performance. The aim of this study was to determine the impact of a stress immunization program on occupational stress of midwives working in health centers. MATERIALS AND METHODS: In this quasi-experimental study, 80 midwives working in health centers of Zahedan (2017) were divided into test and control groups based on random allocation. The intervention involved a stress immunization program consisting of two workshops (each lasting 4 h) in two consecutive weeks, which was implemented for the intervention group. As data collection tool, Health and Safety Executive Occupational Stress Questionnaire was completed in three steps before, immediately after, and 1 month after the intervention. Data were analyzed using descriptive and analytical statistics, independent t-test, and repeated measures ANOVA. RESULTS: The findings showed that mean stress score in the intervention group was increased from 79.5 ± 9.7 before intervention to 104.5 ± 17.3 immediately after it, which was increased to 110.5 ± 18.3 1 month after intervention (P < 0.001). In the control group, mean stress score was decreased immediately after as well as 1 month after the intervention, which was statistically significant after the intervention and 1 month after it (P > 0.023). CONCLUSION: The stress immunization program is an inexpensive and effective way to reduce the stress of midwives; therefore, it is suggested to be used to effectively handle occupational stress among midwives and to improve their quality of care.